2018
DOI: 10.1101/251942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular control of gene expression byBrucellaBaaR, an IclR-family repressor

Abstract: The Brucella abortus general stress response sigma factor, σE1, directly and indirectly regulates the transcription of dozens of genes that influence stress survival and host infection. Characterizing the functions of σE1 regulated genes therefore contributes to understanding of B. abortus physiology and infection biology. Transcription of the IclR family regulator, Bab2_0215, is indirectly activated by σE1 but its function remains undefined. We present a structural and functional characterization of Bab2_0215… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 79 publications
(109 reference statements)
1
1
0
Order By: Relevance
“…Sequencing of the choX1 and choX2 orthologs showed that all the above-summarized characteristics of B. suis bv2 Thomsen were reproduced in Bs2WT. In contrast with ChoX1 and ChoX2, the BSUIS_A0222 encoded protein does not show any of the relevant features described in ChoX of S. meliloti and A. tumefaciens, in accordance with the results presented by Herrou et al (2017) describing the B. abortus BSUIS_A0222 ortholog.…”
Section: Choline Transport Is Active In B Suis Biovarsupporting
confidence: 83%
See 1 more Smart Citation
“…Sequencing of the choX1 and choX2 orthologs showed that all the above-summarized characteristics of B. suis bv2 Thomsen were reproduced in Bs2WT. In contrast with ChoX1 and ChoX2, the BSUIS_A0222 encoded protein does not show any of the relevant features described in ChoX of S. meliloti and A. tumefaciens, in accordance with the results presented by Herrou et al (2017) describing the B. abortus BSUIS_A0222 ortholog.…”
Section: Choline Transport Is Active In B Suis Biovarsupporting
confidence: 83%
“…Similarly, the ChoX1 homolog in B. abortus shows dissociation constants of 7 ± 2 nM for choline and 350 ± 30 µM for betaine, and no specific L-carnitine or L-proline binding (Herrmann et al, 2013). While these types of experiments have not been conducted with B. abortus ChoX2, ligand binding assays performed with B. abortus YehZ (the protein encoded by the homolog of BSUIS_A0222) showed no interaction with glycine betaine, choline, ectoine, or carnitine at low ligand concentration, and only low affinity for glycine betaine (Herrou et al, 2017).…”
Section: Choline Transport Is Active In B Suis Biovarmentioning
confidence: 99%